An Analysis of Frequency and Histopatohologies of Gestational Trophoblastic Neoplasia at Tertiary Care Hospital Peshawar, Khyber Pukhtoonkhwa (KPK) (Journal of Fatima Jinnah Medical University, 2018)
Background: Gestational trophoblastic disease (GTD) encompasses pregnancy related disorders arising from abnormal trophoblast tissue. It consists of premalignant conditions, complete and partial hydatidiform mole and malignant conditions that include invasive mole, choriocarcinoma, placental site trophoblastic tissue and rare epitheliod trophoblastic tumors. The malignant conditions collectively are termed as gestational trophoblastic neoplasia (GTN) or persistent trophoblastic disease (PTD). Objective: To determine the frequency and histopathology of gestational trophoblastic neoplasia, its clinical presentation and management options of this malignant condition. Subjects and Methods: The study was a prospective study conducted at Gynae B Unit, PGMI Lady Reading Hospital, Peshawar from October 2010 to October 2013. Inclusion criterion was, all the patients with history of irregular vaginal bleeding following molar pregnancy, miscarriages, ectopic or term pregnancy or irregular PV bleeding after repeated evacuations, with raised serum beta human chorionic gonadotropin (βhCG). They were evaluated with transvaginal ultrasound, chest x-r ay and Full blood count. After confirmation of molar pregnancy patients were registered, underwent suction evacuation and were counseled regarding disease and disease complications, with stress on contraception with barrier methods and 2 weekly follow up with serum βhCG from same laboratory. Patient’s contact number and home address was taken for sending reminders of follow-up. On follow- up if patient was symptomatic for hemorrhage, pain abdomen, respiratory distress, raised or static serum βhCG, patient was readmitted and further evaluation was done for Gestational trophoblastic neoplasia with full blood count, liver function tests, renal function tests, MRI pelvis, CT chest. Patient was scored to low risk i.e. 6, according to prognostic FIGO scoring. Low risk patients were started on single agent methotrexate/Folinic acid (MTX/FA) and high risk patients were treated in collaboration with clinical oncologist for commencement of multiagent chemotherapy, usually EMA/CO. Results: Total of 123 patients with gestational trophoblastic diseases were included. The mean age was 27±8 years. The gravidity ranged from primi gravida to grand multi gravida, average conception rate being 3.9. The mean gestational age of patients with gestational trophoblastic disease at time of diagnosis and suction evacuation was 12.05±4.5 weeks. Total number of complete hydatidiform moles were found to be 60 (48.7%), partial hydatidiform moles were 14 (11.3%), gestational trophoblastic neoplasia 38 (30%) and in case of 11 (8.9%) follow-up was missing and histopathologies could not be retreated. Among 38 cases of gestational trophoblastic neoplasia, confirmed histopathology suggested 13 (34%) were complete Hmoles, 7(18%) were found to have parital H-moles and retained product of conception, each. Eleven (28.9%) clinically and biochemically behaved as invasive mole, with massive haemorrhage and were followed and treated according to serum βhCG. Conclusion: The frequency of gestational trophpblastic neoplasia is high among patients with gestational trophoblastic disease.
Keywords: Gestational trophoblastic disease, Persistent trophoblastic disease, Serum beta hCG